KONSERVASI TOGA UNGGULAN DESA SUKOSARI DENGAN MATH CITY MAP UNTUK MENGEMBANGKAN USAHA EKONOMI PRODUKTIF BERBASIS OLAHAN TUMBUHAN OBAT - Hidayah, Siti Nurul; Pamungkas, Megita Dwi; Rakhmawati, Gita Puspita; Nindita, Anis; Riyono, Arif Fajar; Al‘fauzi, Muhammad Jibran (LPPM Universitas Bina Bangsa, 2024)
Sukosari village in Bandongan Sub-District, Magelang regency, has great potential in the development and conservation of family medicinal plants (TOGA) thanks to favorable soil and temperature conditions. HIMATIKA Untidar PPK Program aims to maximize this potential through collaboration between students and the community. Activities include program socialization, biodiversity mapping of medicinal plants, TOGA planting and conservation training, as well as traditional herbal medicine making training. The results of this program include the creation of a biodiversity map of medicinal plants, the establishment of TOGA groups and conservation areas, the implementation of TOGA processed product workshops such as turmeric Asam sirih and wedang uwuh, as well as the promotion of traditional herbal medicine through jamutika expo